Research on Improvement in Application Effect of Artificial Fish Nests - LAN Yuqian; ZHANG Jiajun; HE Jingliang; WU Huiying; MA Haitao; WAN Zhengping (Renmin Zhujiang)
As a measure to restore fish habitats,artificial fish nests have been widely used in the protection of aquatic ecosystems.The current studies and inventions of artificial fish nests pay much attention to the changes in material and structural forms,and few focus on their resistance to water flow impact and the convenience of later maintenance.Many problems are exposed in the application of artificial fish nests,such as limited applicable environments,difficulties in adapting to river environments with large changes in flow velocity and water levels,and low process practicability and durability.On the basis of summarizing the application problems of artificial fish nests and their causes,this article explores the applicability characteristics of different artificial fish nests and innovates artificial fish nests sticking to the riverbank through the improvements in structural forms,fixation modes,material selection,and operation to improve the application effects of artificial fish nests in flowing water environment.